Digital Literacy in the Language Centre Classroom - Mike Nelson (Turun Yliopisto; Kieli- ja viestintäopintojen keskus, 2022)
Digital literacy (DL) has become a buzzword in the field of education over the last twenty years. Since its inception in mainstream thought through the work of Gilster (1997), where he put forward the notion of ‘literacy for the digital age’, various competing definitions have emerged (Bawden 2008). Yet perhaps because of the broadness of these varying notions of digital literacy, the concept has remained for many teachers both vague and challenging. Anecdotal evidence suggests that many teachers feel that digital content should form a key part of their teaching but they are uncertain as to exactly how this digital content can best be incorporated into their teaching and even exactly what digital literacy means.
This article examines the perceptions of language centre teachers as to what they believe digital literacy to be, and explores the current practices of language centre teachers in terms of their use of digital media. It also investigates to what extent digital literacy has infiltrated curricula design and the pedagogical approaches adopted by teachers. In all these areas the Jisc Digital Literacy Statements[1] from the teacher and curricula design perspectives were used as guiding frameworks.  This research was carried out as part of the Finelc 2digi project to assist in the development of the digital literacy of language centre teachers in Finland by use of a structured questionnaire distributed to all language centres in Finland. In this way a picture of current practice was obtained, leading to informed digital literacy strategy suggestions based on present and potential practices. The insights gained from this research will hopefully have implications for both future teaching and curricula design.
[1] https://www.jisc.ac.uk/full-guide/developing-digital-literacies